2008
DOI: 10.1158/1078-0432.ccr-08-0393
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with a Recombinant Saccharomyces cerevisiae Expressing a Tumor Antigen Breaks Immune Tolerance and Elicits Therapeutic Antitumor Responses

Abstract: Purpose: Saccharomyces cerevisiae, a nonpathogenic yeast, has been used previously as a vehicle to elicit immune responses to foreign antigens, and tumor-associated antigens, and has been shown to reduce tumor burden in mice. Studies were designed to determine if vaccination of human carcinoembryonic antigen (CEA)-transgenic (CEA-Tg) mice (where CEA is a selfantigen) with a recombinant S. cerevisiae construct expressing human CEA (yeast-CEA) elicits CEA-specificT-cell responses and antitumor activity. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 19 publications
0
77
0
Order By: Relevance
“…They contain the recombinant protein, are heat killed, and are thus relatively safe compared to other forms of cancer therapy [40]. Previous studies have shown that recombinant yeast are efficiently taken up by human or murine DCs, which are consequently matured to express high levels of costimulatory molecules and produce high levels of type I cytokines [41,42]. Preclinical studies have shown that yeast-CEA can activate human CD8 + and CD4 + T cells in vitro , and show anti-tumor activity vs. CEA-expressing murine tumors [33,42].…”
Section: Discussionmentioning
confidence: 99%
“…They contain the recombinant protein, are heat killed, and are thus relatively safe compared to other forms of cancer therapy [40]. Previous studies have shown that recombinant yeast are efficiently taken up by human or murine DCs, which are consequently matured to express high levels of costimulatory molecules and produce high levels of type I cytokines [41,42]. Preclinical studies have shown that yeast-CEA can activate human CD8 + and CD4 + T cells in vitro , and show anti-tumor activity vs. CEA-expressing murine tumors [33,42].…”
Section: Discussionmentioning
confidence: 99%
“…Other IFNs have been tested in immunotherapy approaches. The delivery of INFA in carcinoembryogenic antigen (CEA)-expressing pancreatic tumors cells resulted in major cytotoxicity through CD8 + and natural killer (NK) cells at the tumor site [55]. Moreover, transfer of INFB with a lentivirus in xenograft models resulted in tumor progression inhibition [56].…”
Section: Increasing Immune System Responsementioning
confidence: 99%
“…So far, several yeast genera have been shown to deliver viral or tumor antigens to antigen-presenting cells (APCs). [1][2][3][4][5][6] Besides these proteinaceous antigens, yeast cells are also able to transport antigen-encoding DNA and mRNA to a variety of mammalian APCs. 7,8 An advantage of this yeast-based delivery is the targeted transport of antigenencoding DNA or mRNA directly to APCs, thereby inducing adaptive immune responses such as CD8 + cytotoxic T-cell activation.…”
Section: Introductionmentioning
confidence: 99%